2006
DOI: 10.1038/sj.bmt.1705405
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic lymphocytes and CD34+ cells in cryopreserved cord blood detected by the fluorescent vital dye SYTO 16 and correlation with loss of L-selectin (CD62L) expression

Abstract: Discrimination between live and apoptotic cells is important for accurate determination of viable CD34 þ cells in hematopoietic stem cell transplant products. SYTO16 is a sensitive fluorescent dye for discriminating live from apoptotic leukocytes. The incidence of apoptotic leukocytes in paired samples of fresh and cryopreservedthawed cord blood (CB) was determined by the SYTO16/7-AAD flow cytometric assay. Cell migration and expression of the cell homing molecule L-selectin (CD62L) was determined in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…de Boer et al [60] observed a signifi cant reduction in the quantity of viable CD34 + cells mainly due to early but irreversible apoptosis. Recently, Sparrow et al [61] reported that post-thaw umbilical cord blood samples contained signifi cant portion of apoptotic CD34 + cells and lymphocytes when compared to fresh samples. Since, apoptosis is implicated in the delayed onset of cell death and is accompanied by decline in attachment rate and long-time survival, it is important to perform viability assessment at different time points of post-thaw cultured cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…de Boer et al [60] observed a signifi cant reduction in the quantity of viable CD34 + cells mainly due to early but irreversible apoptosis. Recently, Sparrow et al [61] reported that post-thaw umbilical cord blood samples contained signifi cant portion of apoptotic CD34 + cells and lymphocytes when compared to fresh samples. Since, apoptosis is implicated in the delayed onset of cell death and is accompanied by decline in attachment rate and long-time survival, it is important to perform viability assessment at different time points of post-thaw cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the freeze/thawing process induces extensive early apoptosis stress activation pathways, which can lead to a time-dependent decline in viability and function at culture temperatures [55][56][57][58][59][60][61]. Therefore, consideration must be given to the adoption of methods that simultaneously detect early apoptotic cells along with necrotic cells for a more accurate assessment of post-thaw in this study [62][63][64] and hence ensure the total solidifi cation (and long-term stability) of the frozen sample.…”
Section: Discussionmentioning
confidence: 99%
“…11 The discrepancy could be ascribed to differences among the factors, such as selection of the T cell subsets from frozen/ overnight rested PBMC, which has been showed to induce CD62L shedding with potential biological changes, 36 and subsequent gene modification in those studies. We speculate that different culture conditions such as addition of IL-7 and IL-15 20 and various means of stimulation would also result in differential impacts on the activation and differentiation of T SCM , naive and memory T cells.…”
Section: Cd62lmentioning
confidence: 99%
“…138 For example, de Boer et al 139 observed a significant reduction in the quantity of viable CD34 + cells mainly due to early but irreversible apoptosis. Recently, Sparrow et al 140 reported that post-thaw umbilical cord blood samples contained significant portion of apoptotic CD34 + cells and lymphocytes when compared to fresh samples. Since, apoptosis is implicated in the delayed onset of cell death and is accompanied by decline in attachment rate and longtime survival, it is important to perform viability assessment at different time points of post-thaw cultured cells.…”
Section: Freezing Thawing and Viability Assessmentmentioning
confidence: 99%
“…134,135 Additionally, recent evidence suggests that the freeze-thawing process induces extensive early apoptosis stress activation pathways which can lead to a time dependant decline in viability and function at culture temperatures. [136][137][138][139][140] Therefore consideration must be given to the adoption of methods that simultaneously detect early apoptotic cells along with necrotic cells for a more accurate assessment of number, the published studies mainly focused on developing cryopreservation methods for clinical manufacturing of stem cells derived from amniotic fluid (AF-SCs). In a recently published study which aimed to develop clinical grade manufacturing methods for AF-SCs, it was shown that cryopreservation in the presence of 2.5% human serum AB was efficient in maintaining the post-thaw growth and differentiation potential.…”
Section: Clinical Banking Of Placenta and Amniotic Fluid Derived Stemmentioning
confidence: 99%